Cross-sectional analysis of risk factors associated with the coexistence of three undernutrition indicators among children aged 0–23 months in Tanzania - Edgar Elirehema Pallangyo; Oliva Joseph Kimaro; Nsajigwa Reuben Mwalupani; George Stephen George; Doris Katana; Amina Suleiman Msengwa (BMC Nutrition)
Abstract Background Undernutrition in children under two years is a persistent challenge in Tanzania. This study investigates demographic, maternal, and child-related factors associated with stunting, wasting, and underweight coexistence. Methods Secondary data from 2,158 children aged 0–23 months in the 2022 Tanzania Demographic and Health Survey (TDHS) were analyzed. Risk factors assessed included child age, birth weight, size at birth, birth order, and maternal education. Multinomial regression analysis was conducted to determine associations. Results The risk of coexisting undernutrition was significantly higher among children aged 12–17 months (RRR = 8.297, 95% CI = 1.768–38.931, p = 0.007) and 18–23 months (RRR = 12.860, 95% CI = 2.661–62.152, p = 0.001). Protective factors included birth weight < 2,501 g (RRR = 0.211, 95% CI = 0.056–0.783, p = 0.02), average size at birth (RRR = 0.262, 95% CI = 0.076–0.908, p = 0.035), and higher birth order (2nd–4th: RRR = 0.372, p = 0.023; 5th: RRR = 0.340, p = 0.048). Maternal education emerged as a significant risk factor (RRR = 1.327, 95% CI = 1.128–6.841, p = 0.02). Conclusion This study highlights critical risk factors, including maternal education, child age, and birth characteristics, for the coexistence of stunting, wasting, and underweight. Interventions should target the 12–23-month age group and address maternal education to eradicate child malnutrition in Tanzania.